Malaysian private finance initiative - Najwa , Durizaki (2012)
This research is called "Malaysian Private Finance Initiative". The main purpose of the research is to reveal the process implementation of PH in Malaysia's version. By going through the research, the level understanding Malaysia's version of PFI is identified. Private Finance Initiative (PFI) is implemented in order to help public sector in operate or handle the project with the growth of construction industry in Malaysia. Besides that, the research can identify perception from private sector which involved in construction industry. It is important as the risks are being certified for both public and private sector. The questionnaires surveys are distributed to private sector in Malaysia whether involved or not in handling project under PFI. Questionnaire survey method has been conducted in developing the research because this method is more easy and simple to be analyzed. As a result, the research is done for adding improvement to Malaysia's version of PFI.